2015
DOI: 10.1007/s11999-014-3505-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Surgical Timing Influence Functional Recovery After Lumbar Discectomy? A Systematic Review

Abstract: Background The impact of the duration of preoperative symptoms on outcomes after lumbar discectomy has not been sufficiently answered in a single study but is a potentially important clinical variable. Questions/purposes A systematic review was performed to answer two questions: (1) Does symptomatic duration before surgery influence functional recovery after lumbar discectomy? (2) What is the time point for intervention beyond which the extent of postoperative recovery might be compromised? Methods The systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 12 publications
0
19
2
3
Order By: Relevance
“…Inconsistent findings identified that duration leg pain was not associated with patient outcome [Pain Disability Score, ODI, leg pain, back pain and Clinical Overall Score at 12 months; EQ-5D at 2 and 7 years]. This was in contrast to previous reviews that identified pre-operative duration of leg pain as associated with patient outcome [14,15]. It is however difficult to have confidence in the findings from previous reviews as they themselves were at risk of bias.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Inconsistent findings identified that duration leg pain was not associated with patient outcome [Pain Disability Score, ODI, leg pain, back pain and Clinical Overall Score at 12 months; EQ-5D at 2 and 7 years]. This was in contrast to previous reviews that identified pre-operative duration of leg pain as associated with patient outcome [14,15]. It is however difficult to have confidence in the findings from previous reviews as they themselves were at risk of bias.…”
Section: Discussioncontrasting
confidence: 72%
“…In comparison with other systematic reviews [13][14][15], this review included only prospective cohort studies which are the gold standard design for investigating prognostic factors to enable optimal measurement of outcomes and predictors [42]. Our findings illustrate that the current level of evidence is low/very low.…”
Section: Discussionmentioning
confidence: 86%
“…Die Studien differenzieren meist nicht nach hochgradigen Einschränkungen (Paresen). Sicher scheint, dass die operative Therapie (in einem Kollektiv mit 40 % Paresen) der konservativen Therapie überlegen ist [28], eine Vermeidung langer Symptomatik (Tage bis Monate) scheint weitere Vorteile [29] hinsichtlich der funktionellen Wiederherstellung zu bieten. Eine aktuelle retrospektiv vergleichende Studie, die vor allem schwere motorische Defizite einschloss, konnte einen Vorteil der frühzeitigen Nukleotomie (< 48 h) nachweisen [30] (LoE 2b).…”
Section: Mechanisch Instabile Wirbelsäulenfrakturenunclassified
“…In their 2014 systematic review, Schoenfeld et al concluded that the duration of symptoms quite probably has an adverse effect on pain and functional recovery following lumbar discectomy, with a possible cutoff at 6 months following the onset of symptoms. 17 At the same time, Sabnis et al added that the time with symptomatology alone should not be the basis for a recommendation of surgery, given that there are other variables that negatively affect the outcome, such as social factors (long-standing medical leave, low educational level, single or divorced status), biological (more than 40 years of age) factors, etc. 18 Due to the inconsistent results in the available literature regarding a correlation between duration of symptoms and clinical outcome and to the absence of national studies of this type, we decided to evaluate patients who underwent lumbar discectomy at the Complejo Hospitalario San José (CHSJ).…”
Section: Introductionmentioning
confidence: 99%